Disseminated Histoplasmosis in Children : The Role of Itraconazole Therapy (1996)
ABSTRACT: Objectives: To describe the clinical characteristics and laboratory diagnosis of seven children with disseminated histoplasmosis and evaluate the effectiveness of itraconazole therapy in this severe form of the mycosis as well as to determine the long term results of such treatment. Methods: The diagnosis of histoplasmosis was based on the direct observation of Histoplasma capsulatum var. capsulatum and/or on the isolation of the fungus from pathologic materials; the results of the serologic tests were taken into consideration. Chest roentgenograms also contributed to the diagnosis. Patients: The patients were seven rural children, five girls and two boys, ages 1 to 14 years (mean, 4.6), with a confirmed diagnosis of disseminated histoplasmosis and who had no underlying disease other than malnourishment. Results: The seven children experienced a subacute febrile syndrome for 4 months accompanied by anorexia, weight loss and signs of reticuloendothelial involvement such as lymph node hypertrophy, hepatomegaly and/or splenomegaly. The lung revealed roentgenographic alterations consisting mainly of nodular infiltrates. All patients received itraconazole orally in a mean dosage of 7.2 mg/kg/day, for variable periods (3 to 12 months), depending on the individual response and the toxic effects of the medication. One of the patients who was improving after 1 month of treatment was taken from the hospital by his guardian against medical advice and died shortly afterward. The remaining six patients responded to the treatment with marked clinical improvement and showed negative cultures and decreases in anti-H. capsulatum antibody titers after 3 months of treatment. Only one patient, the youngest and most severely affected child, exhibited hepatotoxicity, which subsided when itraconazole was discontinued. Extended follow-up studies revealed no relapses. Conclusion: The results of this study indicate that itraconazole is effective for treatment of disseminated childhood histoplasmosis. More studies should be performed to determine the most appropriate dosage and the optimal duration of itraconazole treatment in children.